The impact of the COVID-19 pandemic on critically ill patients with acute stroke and diabetic ketoacidosis - Kılıç, Mazlum; Tekyol, Davut (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
Introduction and aim. This study aimed to compare the hospitalization rate, mortality rate and morbidity status of patients hospitalized with stroke and diabetic ketoacidosis (DKA) before and during the COVID-19 pandemic. Material and methods. The data of 2522 patients who applied to the emergency department (ED) before and during the pandemic were evaluated. A Poisson regression analysis was used to examine the number of presentations between two different periods. Results. Stroke cases during the pandemic era were compared to those during the pre-pandemic period, and it was shown that the mortality rate for stroke patients during the pandemic period was much higher. Treatment-related ED presentations decreased significantly during the pandemic period, particularly among patients aged 75–84 years. Rates of ED presentation decreased by 84 percent (IRR: 0.14, 95 percent CI: 0.03-0.59) in those with DKA and by 37 percent (IRR: 0.67, 95 percent CI: 0.53- 0.75) in those with stroke during the pandemic period. Conclusion. Conclusion: Stroke and DKA admissions decreased during the pandemic, but the rate of stroke mortality increased statistically 3.375 times. Getting emergency medical care increases their chances of survival. Even in a COVID-19 outbreak, treatment is critical.
Keywords: diabetic ketoacidosis; strokes; pandemics